The economy today - Schiller, Bradley R. , 1943-; Hill, Cynthia , 1967-; Wall, Sherri (The McGraw-Hill series economics, 2013)
Emphasizes how policymakers must choose between government intervention and market reliance to resolve the core issues of what, how, and for whom to produce. This title presents some of the domestic and global economic news